Penididikan Anak Dalam Surah Luqman (Kajian Tafsir Tematik) - Abd Muqit (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2022)
At this time Indonesia still has problems in the education of children in the religious field. Because Indonesia has a multicultural nation so that there is a tug of war on the concept of education and forcing education policy holders must be able to accommodate educational concepts that are in accordance with the character of the nation. In addition to the influence of globalization and digitalization also has an impact on the character of children's education. To answer this problem, researchers try to conduct research using thematic interpretation methods. The results of this study concluded that Surah Luqman offers an educational concept for a child. The concept of education offered by the surah is the role of the family, especially a father must be involved in the education of children with the method of mauidhah or advice. In addition, surah Luqman also offers the main themes in educating children, namely teaching about tawhid, prayer, patient gratitude, filial piety to parents and good ethics in society.